The Implementation of a Culturally Responsive Teaching Approach Assisted by Data Dice Media to Improve Student Learning Outcomes in Grade V Mathematics in 2025 - Fatikhatus Sangadah (STAIN Bengkalis, 2025)
Classroom Action Research (CAR) aimed at improving the learning outcomes of Grade V students by implementing the Culturally Responsive Teaching (CRT) approach in the Mathematics subject at SD 3 Jati Wetan. The research was conducted in two cycles. The subjects of the study were eight Grade V students, consisting of four boys and four girls. The object of the study was the improvement of students' understanding of data concepts through the Culturally Responsive Teaching (CRT) approach. Data collection techniques included interviews, observation, tests, and documentation. Data analysis was conducted using quantitative data analysis. The cognitive learning outcomes of the students in mathematics showed a significant improvement from the observed (12 %), Cycle I (50%), to Cycle II (88%). Based on the results of the classroom action research, it can be concluded that the implementation of the Culturally Responsive Teaching (CRT) approach assisted by Data Dice media effectively improved students' learning outcomes in Mathematics